Development of interactive e-catalog for history education laboratory in efforts to improve student's digital literation - Sukardi Sukardi; Eva Dina Charunisa; Hermansyah Hermansyah (Journal of Educational and Learning Studies, 2021)
The History Education Laboratory is part of the history education study program, which functions as a learning medium and resource that accommodates the learning process or lectures. The historical education laboratory has a collection of labs that are aimed at helping students' learning process. The existing collections are historical objects from various time periods and historical types, namely local, regional, and international history. This interactive catalog can be accessed virtually by students to help better learning. In addition, the use of this e-catalog also refers to an effort to improve the digital literacy skills of history education students which is still rather minimal. This study uses a development research method with stages, namely, NeedAssessment, Literature Review, Planning, Develop Preminarry Forms of Products, Product Revisions, Preminnary Field Test, and product revisions. In this e-catalog prototype, it is created using a power point and converted to iSpring Suite 8 and website 2 APK Builder. Divided into 4 major groups of collections, namely 1. Praaksara Period, 2. Hindu-Buddhist Period, 3.Islamic Period and 4.Colonial Period. Validated by 3 experts in the field of educational media, language and history education. And tested in a small group of 10 students from the 1st to 2nd and 3rdyears. The e-Kalalog is considered communicative and user friendly. Colonial Period.Validated by 3 experts in the field of educational media, language and history education.And tested in a small group of 10 students from the 1st to 2nd and 3rd years. The e-Kalalog is considered communicative and user friendly. Colonial Period.Validated by 3 experts in the field of educational media, language and history education.And tested in a small group of 10 students from the 1st to 2nd and 3 years. The e-Kalalog is considered communicative and user friendly.